KEPUASAN WISATAWAN TERHADAP PRODUK WISATA UMBUL SONGO UNTUK PENGEMBANGAN WISATA ALAM DI TAMAN NASIONAL GUNUNG MERBABU - , Luluk Catur Nugraharany ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Forest tourism of Umbul Songo is one of main tourism destination that has potential for natural tourism with ecotourism concept that is located in the utilization zone of Merbabu National Park. In their development, the management of this area was not optimal yet and the number of tourist visiting has been experiencing uncertainty. This study aimed to measure the degree of the tourist satisfaction to the quality of tourism product of Umbul Songo and to identify the factors that influencing the tourist satisfaction. The study approach that was used was deductive by quantitative evaluation method. The method for data analysis that was used was (1) CSI analysis to knowing the tourist satisfaction, (2) IPA analysis to knowing the aspects of tourism product which according to the tourist (visitor) is very important in influencing their satisfaction and which aspects that is needed to be increased, and (3) multiple linear regression analysis to knowing the factors which was influencing the tourist satisfaction. The research found several findings : (1) generally, the quality of tourism product of Umbul Songo was perceived had enough quality in offering a satisfaction for the tourist